WATER SKATERS – PREDATORS OF HORSEFLIES (Proceedings of the YSU B: Chemical and Biological Sciences, 2012)
It is established that waterbugs play an important role in reducing the number of horseflies in Armenia. The horseflies are particularly vulnerable to attack while watering at the period of their mass flight. Study results allow recommend tо use waterbugs in the organization of biological control against the blood sucking flies.
Keywords: horseflies; waterbugs; blood sucking flies; biological control